2014
DOI: 10.1155/2014/235930
|View full text |Cite
|
Sign up to set email alerts
|

Matching Biological Mesh and Negative Pressure Wound Therapy in Reconstructing an Open Abdomen Defect

Abstract: Reconstruction of open abdominal defects is a clinical problem which general and plastic surgeons have to address in cooperation. We report the case of a 66-year-old man who presented an abdominal dehiscence after multiple laparotomies for a sigmoid-rectal adenocarcinoma that infiltrated into the abdominal wall, subsequently complicated by peritonitis and enteric fistula. A cutaneous dehiscence and an incontinent abdominal wall resulted after the last surgery. The abdominal wall was reconstructed using a biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…As a consequence, non-cross-linked BP should be used in a sublay position (i.e., with linea alba closure) and cross-linked ones should be preferred when the fascial bridge is needed [ 128 130 ]. BP could also tolerate adjunctive NPWT to facilitate wound healing, granulation, and skin closure [ 131 133 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, non-cross-linked BP should be used in a sublay position (i.e., with linea alba closure) and cross-linked ones should be preferred when the fascial bridge is needed [ 128 130 ]. BP could also tolerate adjunctive NPWT to facilitate wound healing, granulation, and skin closure [ 131 133 ].…”
Section: Methodsmentioning
confidence: 99%
“…Caviggioli et al reported on a patient with a complicated history of peritonitis. An enterocutaneous fistula was created due to enteric leakage [ 91 ]. A large defect of the abdominal wall was reconstructed using a porcine cross-linked mesh.…”
Section: Methodsmentioning
confidence: 99%
“…The difference between polyester and polypropylene is still under debate [163165]. The affinity of different meshes to bacteria has also been studied, and it is established that microporous and multifilament meshes do have a higher affinity for bacterial contamination [165, 166] (EL 2).…”
Section: Resultsmentioning
confidence: 99%